On terms, concepts, theories and strategies in the discussion of greater flexibility of exchange rates - MACHLUP, F. (PSL Quarterly Review, 2014)
The work represents an extensive survey of the issues related to the debate on the exchange rate system. The author make clarifications, proposes distinctions and warns against exaggerated claims in an effort to “clean up” the discussion in order to avoid confusion and provide sharper focus on the issues at hand. The topics dealt with are pegs and parities, alternative exchange rate systems, rate of crawl and width of band, greater flexibility, types of gliding-parity systems, flexible stable invariant, overvaluation undervaluation and the dilemma of advocacy. JEL: E42, F33